Pemanfaatan E-Learning Berbasis Moodle Terhadap Hasil Belajar Siswa Kelas XI IPS Mata Pelajaran Ekonomi di SMAN Bali Mandara - I Wayan Arfian Wiguna; Luh Indrayani (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
This study aims to determine that Moodle-based E-Learning media have an effect on student learning outcomes in class XI IPS at SMAN Bali Mandara. Conducted in August 2019. This study used a quasi-experimental method with pretest and posttest designs. The sample data was collected using Test. The research sample consisted of 30 students for the control class and 30 students for the experimental class. Collecting data using a test instrument in the form of multiple choices, data analysis using the t test. The results obtained by the Independent Sample Test above are guided by the value contained in the